Preparation and Evaluation (In vitro and In vivo) of Mucoadhesive Microspheres of Etoricoxib - Chowdary, K.P.R.; Seetha Devi, A. (Asian Journal of Chemistry, 2011)
Etoricoxib belongs to class II under BCS and exhibit low and variable bioavailability due to its poor aqueous solubility and needs enhancement in dissolution rate and bioavailability to derive its maximum therapeutic efficacy. A novel promising technology for enhancing the bioavailability is a combination of mucoadhesion principle and microsphere technology to result in mucoadhesive microspheres. The objective of the present study is to prepare and evaluate mucoadhesive microspheres for enhancing the dissolution rate and bioavailability of etoricoxib. Mucoadhesive microspheres prepared were in fine discrete powder form. The size of the microspheres was in the range 19-25 μ. Drug content was uniform (C.V < 2 %) in each batch of microspheres prepared. The dissolution of etoricoxib from the mucoadhesive microspheres prepared was rapid and several times higher than the dissolution of the pure drug. A 17.11 and 9.26 fold increase in the dissolution rate (K1) of etoricoxib was observed with hydroxy propyl methyl cellulose (HPMC) and carbopol microspheres respectively when compared to etoricoxib pure drug. The dissolution efficiency was increased from 16.45 % for etoricoxib pure drug to 76.05 and 62.71 % with hydroxy propyl methyl cellulose and carbopol microspheres respectively. Rapid absorption and higher bioavailability of etoricoxib was observed when administered as mucoadhesive microspheres. A 3.52 and 8.05 fold increase in the Ka and 1.86 and 2.06 fold increase in (AUC)∞0 was observed respectively with hydroxy propyl methyl cellulose and carbopol microspheres when compared to etoricoxib pure drug. The mucoadhesive microspheres of etoricoxib prepared employing hydroxy propyl methyl cellulose and carbopol exhibited marked enhancement in the dissolution rate, dissolution efficacy and bioavailability (both rate and extent of absorption) of etoricoxib, a BCS-class II drug.